DUAL HER2 BLOCKADE WITH TRASTUZUMAB AND PERTUZAMB IN HER2- POSITIVE BREAST CANCER: SINGLE CENTER REAL WORLD DATA - Lazareva, Emilija; Smichkoska, Snezhana; Mitreski, Nenad; Klisarovska, Violeta; Stojkovski, Igor; Iljovska, Marina (Journal of Morphological Sciences, 2020)
Agents targeting the human epidermal growth factor receptor 2 (HER2) have improved outcomes of advanced HER2-positive breast cancer with durable responses. We evaluated therapy with trastuzumab and pertuzumab in early and metastatic HER2-positive breast cancer patients.  In this paper we discuss the practicalities of treating patients with this combination with a particular focus on treatment in the single center setting. We retrospectively identifed patients on adjuvant and frst-line anti-HER2 therapy at The University Clinic of Radiotherapy and Oncology Skopje for at least 1 year from 2019 to 2020. Demographics, treatments and adverse events were recorded. The combination of pertuzumabâ€“trastuzumab has established efficacy in patients with HER2â€positive advanced/metastatic breast cancer. Management of treatment related sideâ€effects such as diarrhea, febrile neutropenia and neuropathy typically include dose reduction or switching taxane. Specific patients with poorer tolerance of chemotherapy such may require particular management strategies.The roles of trastuzumab and pertuzumab are now very well established in the frst-line setting; identifying predictors of long-term response to these would be important in selecting which patients might beneft from entry into future clinical trials assessing the long-term beneft of these newer agents in addition.   Keywords: Breast cancer, HER2 positive, Trastuzumab, Pertuzumab.